Present Past : Modernity and the Memory Crisis - Terdiman, Richard (Book collections on Project MUSE., 1993)
This book is about memory-about how the past persists into the present, and about how this persistence has been understood over the past two centuries. Since the French Revolution, memory has been the source of an intense disquiet. Fundamental cultural theories have sought to understand it, and have striven to represent its stresses.